Dancers of the Borovansky Ballet in En Saga, 1941 [1] - Hall, Hugh P. (1941)
Choreography by Laurel Martyn; design by William Constable.
" 6R/25"--In pencil below image.
Condition: Good.
"Hugh P. Hall, 1 St. Georges Road, Elsternwick, Melbourne"--Photographer's stamp on verso.
Part of the collection: Geoffrey Ingram archive of Australian ballet.
Also available online
Keywords: Borovansky Ballet -- Performances -- Photographs; En Saga (Choreographic work : Martyn) -- Photographs; Ballet -- Australia -- Photographs; Ballet dancers -- Australia -- Photographs; Ballet dancers